Investigation of The Models Used and The Accurancy of Exchange Rate Forecasting - Mehta, Dipesh (2010)
Currency forecasting has been the most difficult task in today’s world. Hence, this study compares the forecasting accuracy predicted on the basis of various fundamental and technical models of exchange rate determination. The dissertation is divided into two parts where the first part states the fundamental models which determines the long term determinants of exchange rates and technical models which determines the short run determinants in exchange rate determination where as the second half of the dissertation comments upon the accuracy and inaccuracy of exchange rate forecasting by comparing the actual values and the forecasted exchange rate values. This study also provides some awareness to all the forecasters about some of the financial and non financial factors affecting the exchange rates so as to make appropriate forecasting decisions for the future.